High frequency of Haemophilus influenzae associated with respiratory tract infections among Malaysian Hajj pilgrims - Nik M.N. Nik Zuraina; Abdullah Sarimah; Mohamad Suharni; Habsah Hasan; Siti Suraiya (Elsevier, 2018)
Background: Overcrowding during the annual Hajj pilgrimage has been known to increase the risk of infectious diseases transmission. Despite the high prevalence of respiratory illness among Malaysian Hajj pilgrims, knowledge about the etiologic pathogens is yet very limited. Thus, this study aimed to determine the spectrum of bacterial respiratory pathogens among the Hajj pilgrims returning to Malaysia in year 2016. Methods: Expectorated sputum specimens were collected from the Hajj pilgrims with symptomatic respiratory tract infections (RTIs). Subsequently, the bacterial pathogens were identified using the standard bacteriological culture method and Vitek II system. Results: This study indicated that 255 (87.33%) out of 292 cultured sputa were positive with at least one potential pathogenic bacteria. Out of 345 total bacterial isolates, 60% (n = 207) were Haemophilus influenzae, which was associated with both single bacterium infection (132/173, 76.3%) and multiple bacterial infections (75/82, 91.5%). The other bacterial isolates included; Klebsiella pneumoniae (n = 37, 10.7%), Moraxella catarrhalis (n = 27, 7.8%), Haemophilus parainfluenzae (n = 25, 7.2%), Streptococcus group G (n = 18, 5.2%), Klebsiella spesies (n = 16, 4.6%), Streptococcus pneumoniae (n = 11, 3.2%) and few other organisms. Conclusion: High frequency of H. influenzae was isolated from Malaysian Hajj pilgrims, especially those with respiratory symptoms. Further study should evaluate the actual pathogenicity of the organism and the interactions between the respiratory microbiota towards developing effective prevention strategies of RTIs among the local pilgrims. Keywords: Haemophilus influenzae, Respiratory tract infections, Hajj, Infectious diseases